KUALITAS AKUNTANSI ZAKAT DAN INFAK/SEDEKAH DI BADAN AMIL ZAKAT NASIONAL JAWA TIMUR - Anwar, Achmad Syaiful Hidayat (Univesitas Muhammadiyah Malang, 2018)
This study aims to evaluate Zakat and Infaq/Shodaqoh (ZIS) accounting practices at Badan Amil Zakat Nasional (BAZNAS) of East Java Province. Data collecting technique was done by using open questionnaire and analyzed by using comparative descriptive technique. Based on the analysis result, it can be concluded that ZIS accounting practice in BAZNAS East Java Province has been referring to PSAK 109 but not yet fully applied. Matters not yet implemented include accounting for impairment of zakat and infaq/shodaqoh, non-refundable receipts, non-cash receipts, and ZIS disclosuresKata Kunci: Akuntansi, ZIS, BAZNAS, PSAK 109